PENGARUH DISKUALITAS PELAYANAN TERHADAP NEGATIVE WORD OF MOUTH (WOM) DENGAN KETIDAKPUASAN PASIEN SEBAGAI VARIABEL INTERVENING (Studi Pada Puskesmas Ngesrep Di Kota Semarang) - Donni Renaldy Suratman; Ibnu Widiyanto (Faculty of Economics and Business Diponegoro University, 2016)
This research was motivated by a lot of medical patient complaints after visiting toPuskesmas Ngesrep in form of critics and suggestions. It indicates there areunsatisfactory feelings after their visit to Puskesmas Ngesrep that could be because ofdisquality services from the management. This research is aiming to analyze the effect ofdisquality service medic and non-medic toward patient disatisfaction and negative WOM.This research using descriptive and quantitative for data analyze. The samples for thisresearch are 400 patients that visited Puskesmas Nngesrep. Data was collected usingquestionnaires which tested the validity and reliability. The data was analyzed usingmultiple regression.The result of descriptive analysis shown that disquality service medic, disquality servicesnon-medic, patient’s disatisfaction, and negative WOM Puskesmas Ngesrep classified aslow. Statistical tests shown patient’s disatisfaction variable is affecting positively towardnegatif WOM variable (hypothesis 1 is accepted), disquality service medic variable isaffecting positively toward patient’s disatisfaction (hypothesis 2 is accepted), disqualityservices medic variable is affecting positively toward negatif WOM (hypothesis 3 isaccepted), disquality service non-medic is affecting positively toward disatisfactionpatient’s (hypothesis 4 is accepted), and disquality services non-medic variable isaffecting positively toward intention to negative WOM (hypothesis 5 is accepted).Keywords: disquality service medic, disquality service non-medic, patient’sdisatisfaction, negative WOM.